A rare occurrence of opportunistic infection by Streptococcus mitis due to antibiotic-induced neutropenia in Prosthetic joint infection - Tan, Eng Kee; Ahmad Hanif, Khairil Anwar; Jebasingam Issace, Samuel John; Che-Hamzah, Fahrudin (Springer Nature Group, 2023)
Prosthetic joint infection (PJI) is a devastating complication in arthroplasty surgery. Although the prevalence is less than 2, its functional and financial implications are significant. Part of its treatment involves the usage of prolonged and high-dose systemic antibiotics. Ironically, this predisposes the patient to unwanted adverse effects caused by the drugs. We report a case of cefazolin-induced neutropenia that led to Streptococcus mitis (S. mitis) bacteraemia in a patient with Staphylococcus aureus PJI. There have been no previous reports on cefazolin-induced neutropenic bacteraemia complicating the treatment of PJI. This case report aims to create awareness among the attending physicians on the possibility of cefazolin-induced neutropenia, which led to bacteraemia from an opportunistic microorganism. The reversal was as simple as cessation of the antibiotic itself. However, if not recognized, it could be fatal.